PERAN KEPALA SEKOLAH SEBAGAI SUPERVISI DALAM PENINGKATAN MUTU PENDIDIKAN AGAM ISLAM DI SMP RAUDLATUL MUTA’ALLIMIN - Umar Hasan Hidayatullah; Mohammad Afifulloh; Muhammad Fahmi Hidayatullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study discusses the role of the principal as a supervisor in improving the quality of Islamic religious education at SMP Raudlatul Muta'allimin. This study explains how school principals improve the quality of Islamic religious education by implementing various programs that have been implemented by school principals in the hope that schools can have high quality. This research was conducted using a qualitative descriptive method to analyze the data obtained. Collecting data in this study using various techniques, namely observation, documentation, and interviews. The results obtained in this study are the principal as a supervisor in improving the quality of Islamic religious education at SMP Raudlatul Muta'allimin, namely by having several programs that support the goal of improving education. The principal also carries out various implementations to achieve the existing program objectives. On the other hand, in implementing the program, there are also various supporting factors and obstacles faced by school principals in improving the quality of Islamic religious education.